Synthesis of layered vs planar Mo2C: role of Mo diffusion. (6th January 2022) - Shehzad, M Arslan; Das, Paul Masih; Tyner, Alexander C; Cheng, Matthew; Lee, Yea-Shine; Goswami, P; Dos Reis, Roberto; Chen, Xinqi; Dravid, Vinayak P
Abstract: Chemical vapor deposition growth of metal carbides is of great interest as this method provides large area growth of MXenes. This growth is mainly done using a melted diffusion based process; however, different morphologies in growth process is not well understood. In this work, we report deterministic synthesis of layered (non-uniform c -axis growth) and planar (uniform c -axis growth) of molybdenum carbide (Mo2 C) using a diffusion-mediated growth. Mo-diffusion limited growth mechanism is proposed where the competition between Mo and C adatoms determines the morphology of grown crystals. Difference in thickness of catalyst at the edge and center lead to enhanced Mo diffusion which plays a vital role in determining the structure of Mo2 C. The layered structures exhibit an expansion in the lattice confirmed by the presence of strain. Density functional theory shows consistent presence of strain which is dependent upon Mo diffusion during growth. This work demonstrates the importance of precise control of diffusion through the catalyst in determining the structure of Mo2 C and contributes to broader understanding of metal diffusion in growth of MXenes.